2019
DOI: 10.1002/ajh.25460
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B‐cell lymphoma: 2019 update on diagnosis, risk stratification, and treatment

Abstract: Disease Overview: Diffuse large B-cell lymphoma (DLBCL) is the most common type of aggressive non-Hodgkin lymphoma originating from the germinal center, and it represents a heterogeneous group of diseases with variable outcomes that are differentially characterized by clinical features, cell of origin (COO), molecular features, and most recently, frequently recurring mutations. Diagnosis: DLBCL is ideally diagnosed from an excisional biopsy of a suspicious lymph node, which shows sheets of large cells that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
310
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(345 citation statements)
references
References 94 publications
4
310
0
3
Order By: Relevance
“…Diffuse large B-cell lymphoma (DLBCL) is the most common class of aggressive non-Hodgkin lymphoma originating from the germinal center. It is a heterogeneous group of diseases with variable outcomes that are characterized by clinical features, origin, molecular characteristics, and mutations [16]. DLBCL is a malignancy of large B cells and its incidence is increasing 3 to 4% each year in the US [17].…”
Section: Mir-144 In Diffuse B Cell Lymphomamentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is the most common class of aggressive non-Hodgkin lymphoma originating from the germinal center. It is a heterogeneous group of diseases with variable outcomes that are characterized by clinical features, origin, molecular characteristics, and mutations [16]. DLBCL is a malignancy of large B cells and its incidence is increasing 3 to 4% each year in the US [17].…”
Section: Mir-144 In Diffuse B Cell Lymphomamentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is an aggressive and the most prevalent subtype of non-Hodgkin lymphoma (NHL) (1,2). Despite the improvement of overall outcomes with up-front immunochemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone [R-CHOP]), ∼40% of patients with DLBCL fail to achieve remission and ultimately succumb to death (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In general studies have shown MYC rearrangements to be an adverse prognostic finding, including lower response to standard R-CHOP therapy. 17 While there is a worse prognosis associated with MYC rearrangements in DLBCL, the prognosis is not as poor as when MYC is seen in association with either BCL2 or BCL6 rearrangement (''double-/triple-hit'' lymphomas). 3 Investigation on the rearrangement partner involved in MYC translocations has shown that MYC rearrangements involving immunoglobulin (Ig) genes (IgH, IgK [Ig kappa], or IgL [Ig lambda]) are more likely to be associated with this adverse prognostic risk than rearrangements involving other non-Ig gene partners.…”
Section: Ebv Studiesmentioning
confidence: 99%
“…12 Associations with an increased risk of central nervous system relapse and lower rates of overall survival have been reported. 17,19 Given the lack of a standardized algorithm to define this double-expresser subgroup, the clinical utility of MYC and BCL2 expression by immunohistochemistry is uncertain and likely depends on institutional validation. 11 While polymerase chain reaction (PCR) clonality assessment is not routinely required for the diagnosis of most DLBCLs, a pitfall in this type of analysis includes the presence of clonal T-cell receptor (TCR) rearrangements in up to 33% of DLBCLs due to lineage infidelity.…”
Section: Other Ancillary Studiesmentioning
confidence: 99%
See 1 more Smart Citation